One False Note /Bk 2 - Korman, Gordon (New York : Scholastic, 2008)
Amy and Dan Cahill are in the lead to find thirty-nine clues that safeguard a great power, and are in possession of a coded sheet of Mozart's music that will help them find the next clue while their relatives follow in close pursuit. Does not include game cards.
Booklist, February 2009
Horn Book, October 2009
Resource Links, April 2009
ALA Booklist
Horn Book
Voice of Youth Advocates
Keywords: Mozart, Wolfgang Amadeus, -- 1756-1791 -- Juvenile fiction; Mozart, Wolfgang Amadeus, -- 1756-1791 -- Fiction; Mozart, Wolfgang Amadeus, -- 1756-1791 -- Fiction; Family -- History -- Juvenile fiction; Cryptography -- Juvenile fiction; Genealogy -- Juvenile fiction; Family -- History -- Fiction; Cryptography -- Fiction; Genealogy -- Fiction; Mystery and detective stories; Family -- History -- Fiction; Cryptography -- Fiction; Genealogy -- Fiction; Mystery fiction; Code and cipher stories; Mystery fiction